Can Botulinum Toxin Type A effectively treat neuropathic pain in spinal cord injury?: A protocol of systematic review and meta-analysis. Issue 25 (19th June 2020) - Wang, Zeng-mian; Wang, Ze-yu; Wei, Chun-jie; Jiang, Yao-jia
Abstract: Background: This protocol aims to assess the efficacy and safety of Botulinum Toxin Type A (BTTA) for the treatment of neuropathic pain (NPP) in patients with spinal cord injury (SCI). Methods: We will retrieve databases in Cochrane Library, EMBASE, MEDLINE, Excerpta Medica Database, PsychINFO, the Allied and Complementary Medicine Database, and Chinese Biomedical Literature Database, and China National Knowledge Infrastructure from the beginning to the March 1, 2020. We will consider any potential studies on assessing the efficacy and safety of BTTA for the treatment of NPP in patients with SCI without limitations of language and publication status. Cochrane risk of bias will be used to assess the risk of bias for all included trials. RevMan 5.3 software will be utilized to synthesize the extracted data and to analyze those data. Results: This study will appraise the efficacy and safety based on the current evidence of BTTA for the treatment of NPP in patients with SCI. Conclusion: This study will exert high quality clinical trials for exploring the efficacy and safety of BTTA in treating NPP in patients with SCI. PROSPERO registration number: PROSPERO CRD42020170474.